The Disclosure of Audited Fund Campaign Accounting in Indonesia - Kusumasari, Lita; ., . (International Journal of Engineering and Technology, 2018)
After long history on democracy, Indonesia formed General Elections Commission (Indonesia: Komisi Pemilihan Umum (KPU)) in 1999. KPU is the legitimate body to organize elections in Indonesia.Â  The responsibilities of KPU are deciding the parties that can compete on elections, ruling the voting and the results of seat won for legislatives, president, and mayors in Indonesia. Including the task is set up regulation for campaign and fund campaign accounting. The fund campaign reports are audited using 15 agreed upon procedures by the auditors. The research findings are 42 mistakes from 11 political parties. Only one political party does not make the mistake. The weakness comes from many forms, such as: transpose error, not following the KPU rule no. 17, 2013, the donation is not supported by legal identity, the donation without legal identity is not given back to country, the fund is not placed in special account before used, the candidates submitted fund campaign report without supporting documents, there is error on placing expenditure segment, the sum error, and there is no consistency between one report to another report. The findings on fund campaign reporting from the political parties are analyzed by goodness of fit test (chi-square). The research found that the total mistakes on fund campaign reporting by political parties are same. Based on the result and weakness, KPU need to make it better understanding to political parties by doing training and assisting. The standards of implementation on KPU regulation need to impose so that the quality of fund campaign accounting could be improved. The time frame to report should also be considered.Â
Keywords: audited fund campaign report; campaign; KPU regulation